Patogenicidade do isolado Lins de Trypanosoma vivax em bovinos natural e experimentalmente infectados - Fidelis Junior, Otavio Luiz [UNESP] (2014)
Infections by T. vivax cause great losses to livestock in Africa and Central and South America. Outbreaks due to this parasite have been occurred with increasing frequency in Brazil. Knowledge of changes that occur during the development of disease can be of great value. In order to evaluate clinical signs, parasitemia, hematologic, biochemical, serological and pathological changes caused by T. vivax, three naturally (group N) and three experimentally (group E) infected bovines by T. vivax, with an average weight of 500 and 548 kg, respectively, were studied. The observed prepatent period was two to three days (group E). Animals of group N showed severe weight loss (140 kg). Reduction of erythrocyte numbers, hemoglobin concentration and PCV were observed in group E. WBC showed pronounced changes for group E, such as severe neutropenia and lymphopenia during the acute phase of the illness. Group N showed leukocytosis by neutrophilia. Decrease in total cholesterol, HDL cholesterol, albumin, aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and increased in glucose, globulin, protein, and alkaline phosphatase (ALP) were observed in group E. Animals from group E were positive for both Immunofluorescence Assay (IFA) and for the Enzyme Linked Immunosorbent Assay (ELISA), which did not occur in group N that was positive in IFAT and alternating between positive and negative periods in ELISA. Proteinogram of group E showed initially an increase of ceruloplasmin, which was later reduced, high values of transferrin almost the entire experimental period. On the hand, haptoglobin showed an initial increase with subsequent reduction in group E. In group N, low levels of ceruloplasmin, transferrin and haptoglobin were observed. Histopathological examination showed alterations mainly in were liver, spleen, heart, lung, lymph node, kidney and central nervous system. Changes mainly consisted in mononuclear inflammatory infiltrate in liver ...